[2+2] Photocycloaddition Studies on Complex Tetronic Acid Esters Related to the Synthesis of Cembranoid Diterpenes - Weixler, Roland; Bach, Thorsten (Synthesis, 2014)
Twelve different tetronic acid esters bearing two potentially reactive olefinic groups were prepared and subjected to [2+2] photocycloaddition reactions by irradiation at λ = 254 nm in tert-butanol (5 mM). The diastereoselectivity and regioselectivity of the reaction was studied with regard to the synthesis of cembranoid diterpenes. When the tetronic acid core carried an alk-3-enyl substituent in the γ-position and an alk-3-enyloxy substituent in the β-position, the undesired γ-products prevailed and were formed in 48–81% yield. Altering the γ-alk-3-enyl substituent into an alk-3-ynyl or alk-2-ynyl substituent, resulted in formation of the desired β-photocycloaddition products. The latter products were obtained in yields of 56–88%, with two out of three products exhibiting very high regio- and diastereoselectivity.
Keywords: [2+2] cycloadditions; cyclobutanes; regioselectivity; heterocycles; photochemistry